A small-amplitude study of solitons near critical plasma compositions. (28th November 2016) - Olivier, Carel P.; Verheest, Frank; Maharaj, Shimul K.
Abstract : The properties of small-amplitude solitons are established near critical plasma compositions in a generalized fluid plasma with an arbitrary number of species. The study is conducted via a Taylor series expansion of the Sagdeev potential. It is shown that there are two types of critical compositions, namely rich critical and poor critical compositions. The coexistence of positive and negative polarity solitons is shown to arise at rich critical compositions and near rich critical compositions. At poor critical compositions, no small-amplitude solitons exist, while weak double layers arise near poor critical compositions. A novel analytical expression is obtained for a small-amplitude acoustic speed soliton solution near rich critical compositions. These solitons have a Lorentzian shape with much fatter tails than regular solitons. A case study is also performed for a simple fluid model consisting of cold ions and two Boltzmann electron species. Exact agreement is obtained between the Sagdeev analysis and reductive perturbation theory. For the first time, we derive the same Lorentzian acoustic speed soliton from reductive perturbation theory.